2015
DOI: 10.1007/s00244-015-0140-0
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Phthalate Diesters in Particulate and Vapor Phases in Indoor Air and Implications for Human Exposure in Albany, New York, USA

Abstract: Phthalate diesters are used as plasticizers in a wide range of consumer products. Because phthalates have been shown in laboratory animal studies to be toxic, human exposure to these chemicals is a matter of concern. Nevertheless, little is known about inhalation exposure to phthalates in the United States. In this study, occurrence of nine phthalates was determined in 60 indoor air samples collected in 2014 in Albany, New York, USA. Airborne particulate and vapor phase samples were collected from various samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
63
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(75 citation statements)
references
References 42 publications
6
63
6
Order By: Relevance
“…The median concentration of DEHP in this study is about one order of magnitude smaller than the particle‐bound concentration, 46.2 ng/m 3 , reported by Mandin et al, who analyzed samples collected over 7 days in 285 French dwellings. The significant discrepancy may have resulted from differences in the source strengths of DEHP, ventilation rates, and environmental factors such as indoor temperature between the present study and those in Mandin et al The estimated particle‐bound concentration of BBzP in the current study is slightly lower than the particle‐bound concentration reported in Mandin et al and Trans et al, which is 1.6 and 1.19 ng/m 3 , respectively. The significantly lower particle‐bound concentrations of DMP, DEP, and DnBP observed in our study are most likely due to their high volatility, where more than 90% of these compounds are expected to be found in the gas‐phase rather than particle‐phase .…”
Section: Resultscontrasting
confidence: 85%
“…The median concentration of DEHP in this study is about one order of magnitude smaller than the particle‐bound concentration, 46.2 ng/m 3 , reported by Mandin et al, who analyzed samples collected over 7 days in 285 French dwellings. The significant discrepancy may have resulted from differences in the source strengths of DEHP, ventilation rates, and environmental factors such as indoor temperature between the present study and those in Mandin et al The estimated particle‐bound concentration of BBzP in the current study is slightly lower than the particle‐bound concentration reported in Mandin et al and Trans et al, which is 1.6 and 1.19 ng/m 3 , respectively. The significantly lower particle‐bound concentrations of DMP, DEP, and DnBP observed in our study are most likely due to their high volatility, where more than 90% of these compounds are expected to be found in the gas‐phase rather than particle‐phase .…”
Section: Resultscontrasting
confidence: 85%
“…The extensive use of PAE-containing products results in the release of large amounts of these compounds into the environment. It has been reported that the residues of PAEs were detected in various environmental matrices, such as air (Teil et al, 2006;Tran and Kannan, 2015), soil (Net et al, 2015;Niu et al, 2014), water and sediment (Peijnenburg and Struijs, 2006;Selvaraj et al, 2015). Researchers have indicated that some PAEs have endocrine disruptive effects in animals and humans (Main et al, 2006;Philippat et al, 2015;Zota et al, 2014).…”
Section: Introductionmentioning
confidence: 98%
“…The volume of injection with splitless mode was 1 µL via autosampler with the splitless mode. The chromatographic analysis was similar to that described in earlier reports [4,11]. The temperature of the injector and ion source were set at 280 o C and 230 o C, respectively.…”
Section: The Optimal Conditions Of Gc Analysismentioning
confidence: 99%
“…The oven temperature programmed was started from The MS detector was operated in the selective ion monitoring mode. Ion fragments m/z 149 was monitored for quantification phthalates [4,11]. Ion fragments m/z 177 for DEP, m/z 233 for DiBP and DBP, m/z 279 for DnHP were used for confirmation of the target compounds.…”
Section: The Optimal Conditions Of Gc Analysismentioning
confidence: 99%
See 1 more Smart Citation